Testimonios de pandemia: injusticia epistémica desde la experiencia escolar costarricense - Jiménez Asenjo, Wendy (2023)
To analyze the distance education processes developed during the 2020 school year in Costa Rica, the approaches of epistemicinjustice were applied to the testimonies of families, students, and teaching staff. It is concluded that structural inequalities andadministrative verticality are evidence of epistemic injustice.